Synthesis, Antimicrobial Evaluation and QSAR Studies of 2-chlorobenzoic Acid Derivatives - Mehta, S.; Kumar, P.; Marwaha, R. K.; Narasimhan, B. (Drug Research, 2014)
In the present study, 2-chlorobenzoic acid derivatives were synthesized and evaluated for their antimicrobial activity against Gram-positive bacteria: Staphylococcus aureus, Bascillus subtilis, Gram-negative bacterium Escherichia coli, fungal strains: Candida albicans and Aspergillus niger by tube dilution method. Results of antimicrobial screening indicated that the synthesized compounds exhibited greater antibacterial potential against Gram-negative bacterium (Escherichia coli) than Gram-positive bacteria and the Schiff’s bases of 2-chloro benzoic acid were more potent antimicrobial agents than its esters. Compound 6 (pMICam=1.91 µM/ml, pMICec=2.27 µM/ml) emerged as most potent antimicrobial agent and was found comparable to standard drug norfloxacin (pMICec=2.61 µM/ml) against Escherichia coli. QSAR studies revealed that the antibacterial, antifungal and the overall antimicrobial activities of the 2-chlorobenzoic acid derivatives were governed by the topological parameters, second order and valence second order molecular connectivity indices (2χ and 2χv).
Keywords: antibacterial drugs; antifungal drugs; infectious diseases